Elemento(III) Derivatives of N-(2-Hydroxy-5-Methyl Benzyl) Alanine - Kandpal, Manju; Pratap Pande, Ashutosh; Chandra, Madhup (Asian Journal of Chemistry, 2010)
Several elemento(III) viz. boron, aluminium, iron, arsenic and antimony derivatives of N-(2-hydroxy-5-methyl benzyl) alanine have been prepared via the reactivity of the corresponding elemento (III) isopropoxide with the latter in 1 : 1, 1 : 2 and 1 : 3 molar ratios in benzene medium. All these compounds have been characterized by azeotrope and elemental analyses, as well as by IR and PMR spectral measurements.